Potentials of small garden of double storey linked-houses: thermal performance and healthy environment - Abu Bakar, Aniza (2016)
Linked-houses is a housing type that comes with its front yard and backyard. However, house extension and renovation would used-up these spaces. Hence its potentials as green spaces may have been ignored. Some occupants may ‘abandoned' the front yard and backyard and not using them actively. This paper seeks to study the effect of a green front yard and backyard on the thermal performance of the indoor spaces of linked-houses by comparing the air temperature readings of two units of double-storey linked-houses located in the urban area of Kuala Lumpur. The observation done indicates that heavily planted front yard and backyard gives positive effects on the outdoor and indoor thermal performance of the unit, as well as healthy environment – physically and socially.